Exercise-Induced Modulation of Baroreflex Control of Sympathetic Nerve Activity - Miki, Kenju; Yoshimoto, Misa (Frontiers in Neuroscience, 2018)
Exercise modulates arterial pressure (AP) regulation over various time spans. AP increases at the onset of exercise and this increase is then sustained during exercise. Once exercise is stopped, AP is suppressed for up to an hour afterwards. Prolonged endurance training is associated with dysfunction of the sympathetic regulation of AP in response to posture changes (orthostatic intolerance). Baroreflex control of sympathetic nerve activity (SNA) has been extensively studied to understand the mechanisms underlying exercise-induced changes in AP. We have previously presented entire baroreflex AP-SNA curves during and after exercise, and during central volume expansion, obtained using direct measurements of renal sympathetic nerve activity (RSNA) in conscious animals. In this review, we describe the modulatory effects of exercise on baroreflex control of AP based on these entire AP-RSNA baroreflex curves. We suggest that both acute and chronic exercise can have modulatory effects on the entire baroreflex curve for SNA, and that these effects differ among time periods.